Digital Marketing Strategy in Efforts to Increase ROBAKA Sales Turnover in Karawang MSMEs in the Digitalization Era - Yani, Dini; Isyanto, Puji; Rosmawati, Ery; Apriani, Zenita; Yudha Rahman, Shandikha Arya (Yayasan Pendidikan Belajar Berdikari, 2023)
Toast is a food that is quite popular at all age levels. Consumers can choose a flavor variant that suits their taste. This type of food can be found in several places, including on Jl. HS Ronggo Waluyo No. 72 Sukaharja, East Telukjambe, Karawang. This research uses a qualitative descriptive method with data collection methods using interviews, observation, and decision techniques. The digital marketing carried out by Roti Bakar ROBAKA includes marketing efforts that use electronic devices or the internet. Search Engine Marketing (SEM) Search Engine Marketing, Content Marketing, content automation, social media marketing, and display advertising. The owner of Roti Bakar ROBAKA utilized the existing social media business TikTok and then started making posts with applications and layouts that attracted attention. Posts can be tailored to interesting promotional themes, for example, related to Buy 2 get 1 free, 30-50% discount with applicable conditions or other important dates and days.